People resistance in TQM implementation: a qualitative study on Malaysian universities. (14th January 2008) - Ali, Noor Azman; Zairi, Mohamed; Mahat, Fauziah
The aim of this paper is to discuss the theoretical and research evidence related to the issue of people barriers concerning problems and pitfalls in Total Quality Management (TQM) implementation. The people-based and service-oriented nature of Higher Education (HE) institutions leaves the university leaders and managers for quality projects to look seriously into the cause of the problems, and apply a strategic approach to ensure successful quality initiatives. A qualitative survey on seven universities in Malaysia suggests that the main reasons for people resistance are lack of knowledge and information on the quality programme, lack of motivation and complacency attitudes, and the quality programme being perceived to cause more burden rather that benefit. The relevant human resource management practices and approaches are discussed to overcome the problems.